2017
DOI: 10.1111/dar.12495
|View full text |Cite
|
Sign up to set email alerts
|

Purchases by heavier drinking young people concentrated in lower priced beverages: Implications for policy

Abstract: Heavy consumption of alcohol remains common in New Zealand young drinkers. Heavier drinkers paid less to purchase alcohol and consumed more alcohol in the form of high-potency RTDs. [Wall M, Casswell S, Yeh L-C. Purchases by heavier drinking young people concentrated in lower priced beverages: Implications for policy. Drug Alcohol Rev 2017;36:352-358].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Indeed, research reviewed by Wilsnack and colleagues [44] indicates differences in reasons men and women drink. Notably, research from New Zealand has indicated substantially different drinking patterns between men and women related to location of purchase, beverage choice, and time of consumption [45], which may also reflect differences in social settings. Furthermore, men are consistently found to report more problem drinking across many countries [44] and problem drinking often co-occurs with mental health issues among men [46].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, research reviewed by Wilsnack and colleagues [44] indicates differences in reasons men and women drink. Notably, research from New Zealand has indicated substantially different drinking patterns between men and women related to location of purchase, beverage choice, and time of consumption [45], which may also reflect differences in social settings. Furthermore, men are consistently found to report more problem drinking across many countries [44] and problem drinking often co-occurs with mental health issues among men [46].…”
Section: Discussionmentioning
confidence: 99%